(untitled) (Journal of Medical & Health Sciences Review, 2026)
Diabetes mellitus, characterized by chronic hyperglycemia, increases susceptibility to infections and impairs wound healing. Current treatment options often demonstrate limited efficacy or fail to provide a definitive cure. Nanotechnology presents a promising approach for the development of novel therapeutic materials, particularly in the field of medicine. Among various nanomaterials, copper nanoparticles have gained significant attention due to their unique physicochemical properties and potential biomedical applications. This study investigates the biogenic synthesis of CuNPs using the supernatant of Lactobacillus paracasei and evaluates their therapeutic potential. The biosynthesis of CuNPs through microbial-mediated processes offers an environmentally sustainable and cost-effective alternative to conventional chemical methods. Herein, CuNPs were synthesized using the supernatant of L. paracasei, exploiting its reducing and stabilizing properties. The synthesis was optimized using different concentrations of CuSO₄, with 0.1 M identified as the optimal concentration, as indicated by a color change from blue to dark brown or black. Characterization techniques, including UV–Vis spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray diffraction, were employed to analyze the synthesized CuNPs. The UV–Vis absorption spectra exhibited a peak at 280 nm, confirming the formation of CuNPs, while SEM analysis validated their spherical morphology at the 0.1 M CuSO₄ concentration. The biosynthesized CuNPs demonstrated remarkable therapeutic efficacy, including anticancer, antidiabetic, antimicrobial, antioxidative, and anti-inflammatory properties. Additionally, cytotoxicity assays were conducted to evaluate their potential anticancer activity against HepG2 liver cancer cell lines. These findings highlight the potential of L. paracasei-mediated CuNPs as promising therapeutic agents in healthcare and medicine, paving the way for future biomedical applications.